2014
DOI: 10.1016/j.celrep.2014.08.049
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Functions in Tumor Initiation by Suppressing the Surveillance of Both Innate and Adaptive Immune Cells

Abstract: SUMMARYNF-κB is considered a major contributor to tumor development, but how this factor functions in the initial stages of oncogenesis is not clear. In a model of Ras-induced transformation, we probed NF-κB function as preneoplastic cells formed tumors in mice. As previously shown, the p65 subunit of NF-κB acts as a tumor suppressor in normal cells by sustaining senescence following DNA damage. Our current data reveal that, following immortalization, p65 switches to an oncogene by counteracting the surveillan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 44 publications
1
50
1
Order By: Relevance
“…It has been shown that neutrophils exposed to a combination of G-CSF and IL-6 converted BM neutrophils from a tumor-suppressive to a tumorpromoting phenotype (42). NF-κB-mediated increases in myeloidderived suppressor cells were shown to have a major role in tumor angiogenesis and immune modulation (43). This could underlie the advantage for the tumor cell growth we see in Tle1 Δ/Δ mice.…”
Section: Discussionmentioning
confidence: 75%
“…It has been shown that neutrophils exposed to a combination of G-CSF and IL-6 converted BM neutrophils from a tumor-suppressive to a tumorpromoting phenotype (42). NF-κB-mediated increases in myeloidderived suppressor cells were shown to have a major role in tumor angiogenesis and immune modulation (43). This could underlie the advantage for the tumor cell growth we see in Tle1 Δ/Δ mice.…”
Section: Discussionmentioning
confidence: 75%
“…Although established as an oncogene during the late stages of cancer progression, comparatively little is known about the effects of this pathway at the earlier stages of tumor development. Recent work from our laboratory showed that NF-κB functions as an oncogene by protecting Ras-expressing transformed cells from the actions of infiltrating innate immune cells (10). However, the mechanism by which NF-κB evades the antitumor effects of macrophages has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Work from our laboratory and others have shown that macrophages mediate their killing activity through secretion of the proapoptotic factors TNF and NO (10,18). To confirm this in pancreatic tumor cells, we treated KPC Δp65 both genes ( Figure 7A and Supplemental Figure 7A).…”
Section: Gdf-15 Suppresses Macrophage Cytotoxic Activity By Inhibitinmentioning
confidence: 99%
See 1 more Smart Citation
“…23 This is of interest as NF-κB targets many pro-cancerous genes and plays a vital role in immune response as well. 53 Our study also showed that ectopic overexpression of EPSTI1 in the two noninvasive cell lines, MCF-7 and Implications of epithelial-stromal interaction 1…”
Section: Introductionmentioning
confidence: 66%